Metabolic Effects of Sulphur Derivative Pesticides in Fish Samples of Fresh Water in Bangladesh (Global Journal of Science Frontier Research, 2018)
In Bangladesh, there are lots of fishes in abundance. Fifteen fresh water fish samples namely Puntius sarana (Shawrputi), Channa punctatus (Taki), Wallogonia attu (Boal), Macrognathus aculiatus (Baim), Ailia coila (Kajoli), Mystus cavasisus (Gulsa), Ompok pabda (Pabda),Corica soborna (Kachki), Mystu svittatus (Tengra), Glossogobius giuris (Baila), Macrobrachium malcolmsli (Chingri), Amblypharyngodon microlepis (Mola), Anabas testudineus (Koi), Channa striatus (Shol), Heteropnueste fossilis (Shing). These fish samples were collected from two rivers and a cultured fish pond. The samples were extracted by QuEChERS method, cleaned up with conc. H 2 SO 4 and cleaned extracts were analyzed by GC-ECD. Small size cultured Koi fish sample which did show detectable amount of sulphur containing pesticides and its metabolites was used for the recovery experiments.
Keywords: OSPs; biomagnification; gas chromatography; fresh water fish and food chain